Histological and Biochemical Evaluation of the Protective Potential of Ascorbate and Alpha-Tocopherol against Cypermethrin-Induced Toxicity - Adeniyi, Temidayo; Moronkeji, Akinpelu; Fikayomi, Akinrimisi (Graduate School, Universitas Brawijaya, 2024)
The unrestricted and unsystematic use of cypermethrin pesticides has detrimental effects on the organs, ranging from short-term sickness to long-term effects. The ameliorating effect of alpha-tocopherol and ascorbate was investigated singly and in combination with cypermethrin-induced oxidative stress using murine models. Additionally, the livers and kidneys of rats were histologically evaluated. Twenty-five (25) adult male Wistar rats with an average weight of 190 g were allocated randomly into five groups consisting of five rats each. Group I consists of the unexposed control rats, while rats in groups II-V were the test group exposed to cypermethrin at standard doses of 10 mg.kg-1 bw. While rats in group II were exposed and untreated, group III-V was administered with ascorbate (5000 mg.kg-1 bw), alpha-tocopherol (3000 mg.kg-1 bw), and co-administered with both vitamins at their standard doses, respectively. Regimen administration was by gavage for 28 days, and while the vitamins were administered daily, cypermethrin exposure was done twice a week. At the end of the experiment, rats were euthanized, and blood obtained via cardiac puncture was used for biochemical analysis, while the liver and kidneys excised were processed for histopathological evaluation. Results revealed elevated aspartate transferase (AST), alanine transferase (ALT), malondialdehyde (MDA), and creatinine levels. At the same time, a decrease in superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) activities was observed in the test group (p<0.05). Additionally, treatment with ascorbate and alpha-tocopherol co-administration reversed the biochemical parameters in the exposed rats. Conclusively, ascorbate and alpha-tocopherol ameliorate oxidative damage associated with cypermethrin exposure. Keywords: Cypermethrin, Histopathology, Pesticides, Toxicity, Vitamins.